Advances in the mechanism of different antibacterial strategies based on ultrasound technique for controlling bacterial contamination in food industry. (November 2020) - Dai, Jinming; Bai, Mei; Li, Changzhu; Cui, Haiying; Lin, Lin
Abstract: Background: Pathogenic bacteria contamination has been a global health challenge in the food industry. In this context, ultrasound technique is attracting much more attention as an alternative non-thermal processing method to inactivate pathogens. Compared with traditional thermal process, Ultrasonic Sterilization technology can reduce energy consumption, maintain nutritional content and cause less damage to overall foods quality. Despite ultrasonic sterilization (US) has been proved effective both for its individual and synergistic effect with other antibacterial agents and strategies, but still a knowledge gap exits there in the regulation mechanism of ultrasonic treatment on microorganism physiology that contributes to its application. Scope and approach: Recently, increasing numbers of efficient sterilization strategies based on ultrasound technique have been presented, and the ultrasound-driven cavitation effect has become a promising research direction of US, which can cause a chain of physical and chemical damage to bacterial cells. Therefore, this review mainly discusses the antibacterial effects of US based on its acoustic cavitation combing with mechanical vibration and acoustic streaming, and summarizes the potential antibacterial mechanisms from three fields: sonoporation, sonochemistry and sonoluminescence. Key findings and conclusions: The mechanical stress on bacterial cells, formation of radicals and activation of sonosensitizers induced by acoustic cavitation have been proved as major antibacterial mechanisms in different application strategies of ultrasound to inactivate bacteria, respectively. The information in this review provides the necessary theoretical basis for extending the antibacterial application of ultrasound technique in food processing. Highlights: Ultrasonication can cause physical damage to bacterial membrane. Ultrasonication can promote the penetration of antibacterial agents into bacterial cells. Ultrasonication can produce radicals and cause oxidative damage to bacterial cells. Ultrasonication can activate sonosensitizer by sonochemistry or sonoluminescence.